2009
DOI: 10.1159/000205960
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional State during COPD Exacerbation: Clinical and Prognostic Implications

Abstract: Aims: To estimate the prevalence of malnutrition in chronic obstructive pulmonary disease (COPD) patients hospitalized for exacerbation and to evaluate its clinical and prognostic influence on the exacerbation. Subjects/Methods: The subjects were 78 consecutive patients with moderate-to-severe COPD who were admitted to hospital with a diagnosis of exacerbation. Nutritional status was assessed by means of body mass index (BMI), bioelectric impedance analysis and levels of plasmatic albumin. Previous spirometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 41 publications
3
31
0
3
Order By: Relevance
“…Author in this study suggests the need of nutritional support during COPD [19]. Similarly, a study by Giron et al, reported malnutrition (BMI < 20 kg/m 2 ) in 38% and 40% under the risk of malnutrition among COPD cases [21]. Our study and few other studies shows that malnutrition and risk of malnutrition can be present even in normal BMI among COPD cases [19,22].…”
Section: Discussionsupporting
confidence: 79%
“…Author in this study suggests the need of nutritional support during COPD [19]. Similarly, a study by Giron et al, reported malnutrition (BMI < 20 kg/m 2 ) in 38% and 40% under the risk of malnutrition among COPD cases [21]. Our study and few other studies shows that malnutrition and risk of malnutrition can be present even in normal BMI among COPD cases [19,22].…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies, however, reported on the association between nutritional status and healthcare utilisation, focusing on patients hospitalised for a COPD exacerbation or predictors thereof. The studies showed that being undernourished in COPD is likely to be associated with longer in-patient hospital stays [107,108], a higher probability of being readmitted [62,109] and an increase in healthcare utilisation [110] in comparison with normally nourished patients. Three randomised controlled trials in COPD investigated the effects of nutritional supplementation on healthcare utilisation and/or costs [65,76,111].…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…Studies in patients hospitalized because of COPD exacerbation reported the incidence of cachexia to be as high as 38%. 32 Patients with a lower BMI had a greater lung function decline, higher degree of hyperinflation, and higher serum C-reactive protein levels. 33 In ambulatory patients with exacerbations, no correlations between BMI and exacerbation severity and between the administered treatment and treatment outcome were noted.…”
mentioning
confidence: 92%